Strategi Pengebangan Kemampuan Baca Tulis Hitung Melalui Pembelajaran Motorik: Studi Kasus di SD Inpres Palempang - Dini Dewindah; Rezkyana Tasya Syahda; Imelda (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
Self-development for students in school life is very important to improve, as it will be essential both for themselves and for the country in the future. Motor learning is an activity that involves several internal factors within the human body, such as muscles, nerves, and the brain, which work simultaneously. Through motor learning, children’s skills will improve because of continuous and repetitive activities that train them to perform motor movements correctly. This study aims to determine the level of literacy and numeracy skills (reading, writing, and arithmetic) of students at SD Inpres Palempang, as well as to examine the effectiveness of motor learning on these skills. The research used a descriptive qualitative method. The results of the study identified three innovative learning media that can enhance students’ reading, writing, and arithmetic abilities: 1) Innovative Reading Media: Flannel board media with an alternative alphabet box made from cardboard, 2) Innovative Writing Media: Alphabet flashcards made from cardboard and paper, 3)Innovative Counting Media: A spinning wheel made from plywood.